The 2007 Surveillance Decision : Revised Operational Guidance. (Policy Papers; Policy Paper ;, 2009)
The adoption of the 2007 Decision on Bilateral Surveillance was a landmark for the Fund. Unlike its predecessor, which was focused exclusively on exchange rate policies, the Decision mapped out the full scope of surveillance, including domestic policies. It set out external stability as the organizing principle for surveillance, and was thus expected to promote focus on issues central to the Fund's mandate, including monetary, fiscal, and financial sector policies and increased attention to exchange rate issues. Surveillance under the Decision was intended to promote candor through clear assessments of the economic situation, outlook, and vulnerabilities of members and clear policy recommendations in pursuit of domestic and external stability.